2015 IEEE Power &Amp; Energy Society Innovative Smart Grid Technologies Conference (ISGT) 2015
DOI: 10.1109/isgt.2015.7131785
|View full text |Cite
|
Sign up to set email alerts
|

Impact of wind turbine generator type in large-scale offshore wind farms on voltage regulation in distribution feeders

Abstract: The goal of the U.S. Department of Energy (DOE) roadmap [1] is a 20% penetration of wind energy into the generation mix by 2030. Attaining this objective will help protect the environment and reduce fossil fuel dependency, thus improving energy security and independence. This paper discusses how the technology used in large scale offshore wind farms impacts voltage regulation in distribution feeders. Although the offshore wind farms are integrated into an interconnected power system through transmission lines,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…In steady-state stability analysis, a main concern associated with the integration of wind and solar power plants is the intermittent/stochastic nature of the power produced, increasing the uncertainty associated with power system states and the attendant complexity of power system (Sajadi, Kolacinski, & Loparo, 2015). This includes active power and reactive power availability and the power flow across the system.…”
Section: Normal Operationmentioning
confidence: 99%
See 1 more Smart Citation
“…In steady-state stability analysis, a main concern associated with the integration of wind and solar power plants is the intermittent/stochastic nature of the power produced, increasing the uncertainty associated with power system states and the attendant complexity of power system (Sajadi, Kolacinski, & Loparo, 2015). This includes active power and reactive power availability and the power flow across the system.…”
Section: Normal Operationmentioning
confidence: 99%
“…Following the integration and operation of renewable power plants in the transmission level, the control of distribution feeders can be affected. This can be characterized into a variety of reasons: (a) change of power flow across the system as a result of redispatch of power plants, (b) new points of power injection (resulted by displacement or replacement of power plants), and (c) topological changes in the system (Sajadi et al, 2015). Figure 8 displays the influence of the integration of a 1,000 MW offshore wind power plant in the PJM transmission system on voltage regulation in the FirstEnergy's distribution feeders.…”
Section: Interference Between Transmission and Distribution Systemsmentioning
confidence: 99%
“…These are power electronics based high frequency switching devices combined with passive elements to mitigate PQ issues by controlling the network parameters [31]. Among those devices, static synchronous compensator (STATCOM), static VAR compensators (SVC), dynamic voltage restorer (DVR), and unified power flow controller (UPFC) are effective in resolving PQ issues like harmonics, load unbalancing and to retain voltage regulation [32]- [34]. The DVR, when employed with a proper control scheme, is an efficient device for rectifying power fluctuations occur due to intermittent wind energy.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have investigated the effects of wind power plant integration on power system operation and have recommended various techniques for steady-state analysis, but mainly for land-based wind generation and the integration into distribution and sub-transmission systems. The authors of [2] introduced an error-based index to measure voltage regulation with implications of how different types of offshore wind generators can impact voltage regulation in distribution feeders when integrating a wind power plant at the transmission level. This study suggested that voltage regulation in distribution feeders is a function of location of the point of interconnection (POI).…”
Section: Introductionmentioning
confidence: 99%